Donation after circulatory death transplantation: a systematic review and meta-analysis of outcomes and methods of donation - Jolliffe, Jarrod; Brookes, John; Williams, Michael; Walker, Elizabeth; Jansz, Paul; Watson, Alasdair; MacDonald, Peter; Smith, Julian; Bennetts, Jayme; Boffini, Massimo; Loforte, Antonio (Annals of Cardiothoracic Surgery, 2025)
Background: Heart failure remains a significant cause of morbidity and mortality internationally. With significant disparities in supply and demand for donor organs and recipients, there has been a growing need to expand the donor pool. Donation after circulatory death (DCD) heart transplantation offers such a method, with ex-situ machine perfusion (ESMP) and thoracoabdominal normothermic reperfusion (NRP) offering two potential methods of procuring DCD organs. This systematic review and meta-analysis aims to evaluate the current literature and compare DCD with donation after brain death (DBD) as well as DCD methods of transplantation. Methods: A systematic literature review was performed according to PRISMA guidelines. Primary outcomes were 30-day, 6- and 12-month survival, as well as primary graft dysfunction (PGD) and acute rejection. Secondary outcomes were length of stay (LOS), intensive care unit (ICU) LOS and temporary dialysis. Weighted averages were utilised to summarise data with funnel plots utilised for comparisons. Reconstructed Kaplan-Meier curves were utilised to evaluate mid-term survival. Results: A total of 10 studies were included evaluating 923 DCD recipients and 7,236 DBD recipients. Survival for DCD and DBD patients at 6 months was 93% and 91% respectively [odds ratio (OR), 1.5; 95% confidence interval (CI): 1.0–2.2; P